Cultural Policy - Significant Challenges of the Georgian Government - Manana Darchashvili; Nino Nishnianidze; Emilia Alaverdov (European Scientific Journal, ESJ, 2019)
The paper examines and discusses the role and place of culture in the formation of a modern peaceful environment based on the study of empirical material. Culture is presented - as the World’s Sustainable Development – in the field of economical activation and empowerment of social and environmental components; the importance of Georgian culture and its interconnection with tourism, as it fosters the promotion, and at the same time, draws a special interest toward the cultural tourism. This creates a common promotion of cultural tourism and contributes to the preservation of cultural heritage, the establishment of harmony and mutual understanding between people; is studied the development of cultural tourism attractions. Georgia's example demonstrates the importance of UNESCO-led projects and collaborations on unique cultural features; it aims to preserve the history of statehood and its originality, respect independence and faiths, etc., thus, promoting them in the world. The data presented in the paper show that with the active involvement of the authorities the current year (2019), (despite the problem in the country’s tourism sector) the positive trend of the increasing number of visitors has been maintained in the protected areas of the Ministry of Environment and Agriculture. The paper examines the efforts of Georgian authorities to create a certain environment and a fertile ground for the preservation of national heritage, cultural diversity and its new perceptions, the development of creative activities and the diversification of cultural life.